Implikasi Putusan Mahkamah Konstitusi Terhadap Penguatan Hak Masyarakat Adat Atas Tanah Dan Sumber Daya Alam - Sugianto, Gianinda Audrine (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The attention of various parties to the existence of customary law communities has recently been getting stronger. This is a form of implication of constitutional recognition and respect for customary law communities and their traditional rights as based on the 1945 Constitution of the Republic of Indonesia (UUD 1945). This recognition was further strengthened by the Constitutional Court (MK) through its decisions in the examination of various laws related to land and natural resources. Ironically, of the many decisions made by the Constitutional Court, particularly related to land and natural resources, there are still many substance changes to laws that are decided by the Constitutional Court which are not fully accommodated by state administrators. That is why, there are 3 (three) problem indicators that need to be seen as well as parameters in determining the implications of the Constitutional Court's decision on strengthening the rights of indigenous peoples to land and natural resources. First, to see how much the implications of the Constitutional Court's decision relating to strengthening the rights of indigenous peoples to land and natural resources affect every policy on public services provided to the community. Second, the judiciary as a gateway to seeking justice should also be a parameter of how much the implications of the Constitutional Court's decisions relating to strengthening the rights of indigenous peoples to land and natural resources are adopted by judicial decisions, especially in the world of general justice. Third, concerning the concern of lawmakers in accommodating every decision of the Constitutional Court into the legislative process concerning the rights of indigenous peoples to land and natural resources. The reason is, this is proven by the cancellation of several articles of various sectoral laws because they are considered not to comply with the mandate of the 1945 Constitution. This study uses a normative legal research method with descriptive research specifications and is analysed through literature study and data analysis methods using juridical- qualitative. The results obtained from this study are that every decision made by the Constitutional Court, especially regarding land and natural resources, should be fully accommodated by state officials based on these three indicators. So that the Constitutional Court's decision is really a solution and answer for indigenous peoples in maintaining the existence of rights to and natural resources. Thus, a policy blueprint is needed to implement each of the decisions of the Constitutional Court, especially on the Rights of Indigenous Peoples to Land and Natural Resources.